Nitric oxide emission during the reductive heterogeneous photocatalysis of aqueous nitrate with TiO2 - Montesinos, Victor Nahuel (2015)
For the first time, nitric oxide (NO), a precursor of nitrogen dioxide (NO2, a NIOSH-listed atmospheric pollutant), has been found to be one of the final products of the photocatalytic reduction of nitrate in water using TiO2 and formic acid as a hole scavenger.